Radiocarbon-dating adhesive and wooden residues from stone tools by Accelerator Mass Spectrometry (AMS): challenges and insights encountered in a case study. (September 2015) - Yates, A.B.; Smith, A.M.; Bertuch, F.; Gehlen, B.; Gramsch, B.; Heinen, M.; Joannes-Boyau, R.; Scheffers, A.; Parr, J.; Pawlik, A.
Abstract: In this study we present and assess a process to enhance archaeological residue AMS dating by focusing on contaminant confinement. The sequence of methods applied consists of: 1) optical residue and use-wear analyses, 2) experimental designs addressing cleaning treatments to mitigate impact of contaminants, 3) preparation and extraction of residues from (mostly) previously dated stone artefacts, and 4) establishing the elemental characteristics of residues by using SEM/EDX as a final step to avoid sample contamination during analyses. We found the alkaline surfactant Decon 90 is a useful solution for removal of skin scales and fabric fibre but has limited effect on graphite contamination introduced by pencil lead. Adhesive residues were not affected by Decon immersion, however, wooden residues from bog sites were partly dislodged. While the methodological sequence was in general successful and some artefact residues were dated within the anticipated age range, difficulties were encountered with other lithic residues. Some artefact residues attained AMS dates which appear to be affected by modern contaminants and other residue radiocarbon dates were seemingly affected by fossil shell derived from flint stone, plasticizers or from a fixative substance older than the fabrication and use of the artefact. One outcome from this study is that performing chemical residue identification earlier in the method sequence using non-destructive and non-contaminating methods would guide the choice of residue treatment and improve reliability of age determination. Highlights: A methodological sequence to enhance lithic residue AMS dating is presented. Experimental design to evaluate cleaning and extraction techniques. AMS radiocarbon dates on ahesive and wooden residues from previously dated lithics partially overlap, partially deviate. Contaminants identified but partially influence residue dates. Light microscopy and SEM-EDX analyses complementary methods in residue characterization.